Recent Advances in Enantioselective Organocatalytic Reactions Enabled by N-Heterocyclic Carbenes (NHCs) Containing Triazolium Motifs - Sharma, Deepika; Chatterjee, Rana; Dhayalan, Vasudevan; Dandela, Rambabu (Synthesis, 2022)
N-Heterocyclic carbenes (NHCs) containing triazolium motifs have emerged as a powerful tool in organocatalysis. Recently, various NHC-catalyst-mediated organic transformations have been developed. This review aims to compile the current state of knowledge on enantioselective NHC-triazolium-catalyzed named reactions as well as introduce newly developed catalytic methods. Furthermore, this review article framework provides an excellent opportunity to highlight some of the unique applications of these catalytic procedures in the synthesis of natural products and biologically active compounds, notably the extensive processes for the preparation of substituted chiral alcohols and their derivatives. This review also provides an overview of the synthesis of chiral NHC-triazolium-catalyst libraries and their applications in catalytic enantioselective reactions.1 Introduction2 Synthesis of N‑Heterocyclic Carbenes Containing Triazolium Motifs2.1 Pyrrolidine-Based Triazoliums NHCs: Px2.2 Morpholine-Based Triazoliums NHCs: Mx2.3 Aminoindane-Based Triazoliums NHCs: AMx2.4 Oxazolidine-Based Heteroazoliums NHCs: Ox2.5. Acyclic Triazoliums NHCs: Ax3 Enantioselective Organocatalytic Reactions3.1 Enantioselective Benzoin Reactions3.1.1 Aldehyde–Aldehyde Homo-Benzoin Reactions3.1.2 Aldehyde–Aldehyde Cross-Benzoin Reactions3.1.3 Aldehyde–Ketone Cross-Benzoin Reactions3.1.4 Aldehyde–Imine Cross-Benzoin Reactions3.1.5 Aza-Benzoin Reactions3.2 Enantioselective Stetter Reactions3.2.1 Intramolecular Stetter Reactions3.2.2 Intermolecular Stetter Reactions3.3 Enantioselective Diels–Alder Reactions3.4 Enantioselective Michael Additions3.5 Enantioselective Rauhut–Currier Reactions3.6 Enantioselective Cycloadditions3.7 Enantioselective Michael–Stetter Cascade Reactions3.8 Enantioselective Annulation Reactions3.9 Synthesis of Spiro Compounds3.10 Heterocycle Synthesis3.11 Carbocycle Synthesis3.12 Asymmetric Steglich Rearrangement Reactions3.13 NHC-Mediated Asymmetric Acylation/Hydroacylation Reactions3.14 Enantioselective α-Fluorination of Aliphatic Aldehydes3.15 Functionalization of Carboxylic Anhydrides by NHC Catalysis3.16 Asymmetric β-Boration of Acyclic Enones3.17 Synthesis of Tropane Derivatives via Organocatalysis3.18 Dynamic Kinetic Resolution of Pyranones via NHC Catalysis3.19 Enantioselective Umpolung Reactions3.20 Enantioselective Esterification of Ketenes3.21 Asymmetric Synthesis of trans-γ-Lactams3.22 Oxy-Cope Rearrangements3.23 Claisen Rearrangements3.24 Enantioselective Synthesis of Complex Heterocycles3.25 Atroposelective Synthesis of N-Aryl Succinimides3.26 Asymmetric α-Fluorination via Cascade Reactions4 Conclusion
Keywords: asymmetric synthesis; organocatalysis; N-heterocyclic carbenes; triazolium motif; chiral alcohols